A Microsurgical Technique for Removing the Spermatheca of Bumblebee Females and Its Application - Mingsheng Zhuang; Fan Yang; Zhongyan Xia; Yu Fei; Fugang Liu; Zhengyi Zhang; Zhihao Zhang; Jilian Li (Insects)
To solve the technical bottleneck caused by the absence of a feasible method for removing the spermatheca in social insects, we developed a microsurgical technique specifically designed for bumblebee females. In this study, the invention of this technique is based on the anatomical characteristics of the sting chamber of bumblebees and uses a bespoke scalpel to precisely remove the spermatheca, which is small in size and deeply embedded within the body. During the removal operation, a small wound was observed and a small amount of hemolymph flowed out. The wound healed very quickly and the survival rate of treated individuals was high. The results showed that there was no significant impact on the critical life activities of queens and workers, including longevity, mating behavior, oviposition capacity, and overwintering survival rate after the spermatheca was removed using this technique. These findings further confirm the feasibility and applicability of the technique and provide strong technical support for exploring the evolutionary dynamics and potential function of the spermatheca in social insects.